Do dimethyl fumarate and nicotinic acid elicit common, potentially HCA2‐mediated adverse reactions? A combined epidemiological‐experimental approach. Issue 10 (24th March 2021) - Dubrall, Diana; Pflock, René; Kosinska, Joanna; Schmid, Matthias; Bleich, Markus; Himmerkus, Nina; Offermanns, Stefan; Schwaninger, Markus; Sachs, Bernhardt
Abstract : Aim: Dimethyl fumarate and nicotinic acid activate the hydroxy‐carboxylic acid receptor 2 (HCA2 ) and induce flushing. It is not known whether HCA2 mediates other adverse drug reactions (ADRs) to these two substances. This study aims to compare ADRs associated with dimethyl fumarate and nicotinic acid, and to discuss whether they are HCA2 ‐mediated. Methods: We identified spontaneous reports of suspected ADRs to dimethyl fumarate and nicotinic acid in the European Adverse Drug Reaction Database (EudraVigilance). These reports were analysed at different hierarchical levels of the Medical Dictionary for Regulatory Activities (MedDRA). In addition, we screened murine organs for HCA2 expression. Results: Similarities in the ADR profile of dimethyl fumarate and nicotinic acid included "gastrointestinal signs and symptoms" (odds ratio [OR] 0.8 [0.6‐1.1]), "hepatobiliary investigations" (OR 1.3 [0.7‐2.5]) and "anxiety disorders and symptoms" (OR 0.9 [0.3‐2.2]) in High Level Group Terms; "diarrhoea (excluding infective)" (OR 1.2 [0.7‐1.8]) and "liver function analyses" (OR 1.3 [0.7‐2.6]) in High Level Terms; and "diarrhoea" (OR 1.2 [0.7‐2.0]) and "vomiting" (OR 0.9 [0.4‐1.7]) in Preferred Terms. In analogy, HCA2 was expressed in the gastrointestinal tract, liver and central nervous system (CNS) of murine organs. A discrepant ADR profile was seen for "lymphopenia" (n = 777) at the preferred term level (only reported for dimethyl fumarate) and "blood glucose increased" (more often reported for nicotinic acid; OR 0.1 [0.0‐0.5]). Conclusion: The gastrointestinal ADRs common to both substances may be mediated by HCA2 . Other ADRs not common to both substances are compound or indication‐specific reactions and likely do not involve HCA2 .